New Multicultural Identities in Europe Religion and Ethnicity in Secular Societies - Toguslu, Erkan (Current Issues in Islam, 2014)
How to understand Europe's post-migrant Islam on the one hand and indigenous, anti-Islamic movements on the other? What impact will religion have on the European secular world and its regulation? How do social and economic transitions on a transnational scale challenge ethnic and religious identifications? These questions are at the very heart of the debate on multiculturalism in present-day Europe. Through the lens of post-migrant societies, manifestations of identity appear in pluralized and deterritorialized forms. This calls into question the nature of boundaries between, as well as within various ethnic-religious groups. Although the contributions in this volume focus on Islam, attention is also paid to Christianity, Judaism, and Hinduism. The authors present empirical data from cases in Turkey, Germany, France, Spain, the United Kingdom, Poland, Norway, Sweden and Belgium, and sharpen the perspectives on the religious-ethnic manifestations of identity in 21st-century Europe.